2014
DOI: 10.1111/tpj.12494
|View full text |Cite
|
Sign up to set email alerts
|

RhHB1 mediates the antagonism of gibberellins to ABA and ethylene during rose (Rosa hybrida) petal senescence

Abstract: SUMMARYRose (Rosa hybrida) is one of the most important ornamental plants worldwide; however, senescence of its petals terminates the ornamental value of the flower, resulting in major economic loss. It is known that the hormones abscisic acid (ABA) and ethylene promote petal senescence, while gibberellins (GAs) delay the process. However, the molecular mechanisms underlying the antagonistic effects amongst plant hormones during petal senescence are still unclear. Here we isolated RhHB1, a homeodomain-leucine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(78 citation statements)
references
References 60 publications
8
70
0
Order By: Relevance
“…Previous studies have reported that HD-Zip I transcription factors are involved in abiotic stress responses (Ariel et al, 2010), fruit ripening (Lin et al, 2008), and leaf and flower senescence (Manavella et al, 2006;Lü et al, 2014). Here we showed that RhHB6 acts as a regulator of RhPR10.1, and that its expression was also up-regulated in senescent rose petals and involved in ethylene-induced flower senescence (Figs.…”
Section: Rhpr101 Inhibits Ethylene-induced Rose Flower Senescence Thsupporting
confidence: 57%
See 4 more Smart Citations
“…Previous studies have reported that HD-Zip I transcription factors are involved in abiotic stress responses (Ariel et al, 2010), fruit ripening (Lin et al, 2008), and leaf and flower senescence (Manavella et al, 2006;Lü et al, 2014). Here we showed that RhHB6 acts as a regulator of RhPR10.1, and that its expression was also up-regulated in senescent rose petals and involved in ethylene-induced flower senescence (Figs.…”
Section: Rhpr101 Inhibits Ethylene-induced Rose Flower Senescence Thsupporting
confidence: 57%
“…3A). In addition, the ion leakage rate and expression of the senescence marker gene RhSAG12 (Lü et al, 2014) were significantly higher in RhPR10.1-silenced petal discs than in the TRV control (Fig. 3, B and C).…”
Section: Silencing Of Rhpr101 Accelerates Rose Flower Senescencementioning
confidence: 91%
See 3 more Smart Citations